An Analysis of Ideological Messages in President Debate: An Applied Linguistics Study - Laba, I Nengah; Doloksaribu, Michelle Jacqueline; Nawung, Agnes Nawung (International Journal of Linguistics and Discourse Analytics, 2024)
The purpose of this study is to investigate the utilization of applied linguistics in the 2024 presidential debate in Indonesia. The data collection for this research doesn't involves individual participation. This study differs from previous ones that addressed related subjects because of the unique analytical approach that was used. The process of analysis includes going over and contrasting earlier research. In applied linguistics, the term "language and ideology" refers to the study of the relationships between language use and social norms, values, and power dynamics. The analysis process encompasses reviewing and comparing prior studies. Language and ideology in applied linguistics refer to the study of how language use is intertwined with societal beliefs, values, and power structures. It is found out that language reflects, shapes, and is shaped by prevailing ideologies in diverse contexts. All these aspects are depicted through description, interpretation, and analysis. Moreover, the relationship between language and ideology in applied linguistics involves examining how linguistic choices and practices contribute to the construction, reinforcement, or challenge of societal norms and beliefs.